Nursing Students’ Reflections on English Role-Play Activities in ESP Class - Nurizzi Rifqi Ferdian; Bayu Nirwana (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The use of role-play as a learning method is applied and maximized by teachers to facilitate students in learning English. This study aimed to explore the nursing students’ reflections towards role-play activities in ESP class on what perceptions they have and how they perceive role-play. There are 60 nursing students from English for Specific Purposes (ESP) class at Politeknik Negeri Subang participate in this study. The data were collected via the questionnaire and the focus group discussions with 10 volunteered students. The questionnaire analysis results revealed that most students had learning enthusiasm ẍ=3,55 in learning English using role-play, enjoy role-play as an effective activity ẍ=3,65, and role play can improve their communication skill ẍ=3,59. The data from focus group discussions revealed that the students perceived that role-play is their English needs as nurses, as the encouragement from teachers for students to speak English, and as a means to facilitate them to be communicative in English. The students’ reflections displayed that role-play is certainly suggested and considered appropriate for vocational institutions that need much direct learning for their profession since it entirely supports them to achieve in accomplishing their professional careers.